Extracellular Vesicles: Role in Inflammatory Responses and Potential Uses in Vaccination in Cancer and Infectious Diseases - João Henrique Campos; Rodrigo Pedro Soares; Kleber Ribeiro; André Cronemberger Andrade; Wagner Luiz Batista; Ana Claudia Torrecilhas (Journal of Immunology Research)
Almost all cells and organisms release membrane structures containing proteins, lipids, and nucleic acids called extracellular vesicles (EVs), which have a wide range of functions concerning intercellular communication and signaling events. Recently, the characterization and understanding of their biological role have become a main research area due to their potential role in vaccination, as biomarkers antigens, early diagnostic tools, and therapeutic applications. Here, we will overview the recent advances and studies of Evs shed by tumor cells, bacteria, parasites, and fungi, focusing on their inflammatory role and their potential use in vaccination and diagnostic of cancer and infectious diseases.